Genome-wide association study of the age of onset of type 1 diabetes reveals HTATIP2 as a novel T cell regulator - Cardinale, Christopher J.; Chang, Xiao; Wei, Zhi; Qu, Hui-Qi; Bradfield, Jonathan P.; Polychronakos, Constantin; Hakonarson, Hakon (Frontiers in Immunology, 2023)
Type 1 diabetes is more difficult to manage when it presents at a younger age, motivating us to identify genetic correlates of the age-of-onset. We conducted the first genome-wide association study of type 1 diabetes treating the age at diagnosis as a quantitative trait. Using a discovery cohort of 4,014 cases and a replication cohort of 493 independent cases, we discovered two loci that were significantly associated: the previously-identified signal in the human leukocyte antigen locus on chromosome 6, and a novel signal in the NELL1 gene on chromosome 11. Bayesian fine-mapping nominates rs10833518 as the causal SNP. Homozygosity for the risk allele is associated with an average onset of diabetes one year earlier (P = 1.54 × 10-9). The risk allele of this SNP is bound by an allele-specific protein complex in a gel shift experiment. Four genes in this locus are expressed in immune cells. We used siRNA knock-down of these candidates and assessed the impact with RNA-seq in primary human CD4+ T cells. Inhibition of HIV TAT-interacting protein 2 (HTATIP2), but not PRMT3, FANCF, or SVIP, modifies gene expression, affecting multiple signal transduction pathways. Knock-down or overexpression of HTATIP2 affects primary T cell viability, proliferation, and the expression of the early activation marker CD69. This study implicates HTATIP2 as a new type 1 diabetes risk gene acting via T cell regulation.